2003
DOI: 10.4049/jimmunol.171.12.6936
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Mediates Estrogen’s Immune Protection in Autoimmune Disease

Abstract: Estrogens are known to influence a variety of autoimmune diseases, but it is not known whether their actions are mediated through classic estrogen receptor α (ERα). The presence of a functional ER was demonstrated in secondary lymphoid tissues, then ERα expression was shown at both the RNA and protein levels in these tissues. Use of ERα knockout mice revealed that both the estrogen-induced disease protection and the estrogen-induced reduction in proinflammatory cytokines were dependent upon ERα in the prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 43 publications
11
124
0
3
Order By: Relevance
“…In contrast, an ER -selective agonist had little to no effect on disease. This suggests that the effects of estrogens on disease in the EAE model are mediated primarily through ER and are consistent with the recently reported findings that the immunosuppressive effects of E2 and estriol are dependent upon ER (Liu et al 2003, Polanczyk et al 2003. Further, we show that SERMs, which are non-steroidal ER ligands that have tissue-selective mixed agonist/antagonist activity, also suppressed EAE.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, an ER -selective agonist had little to no effect on disease. This suggests that the effects of estrogens on disease in the EAE model are mediated primarily through ER and are consistent with the recently reported findings that the immunosuppressive effects of E2 and estriol are dependent upon ER (Liu et al 2003, Polanczyk et al 2003. Further, we show that SERMs, which are non-steroidal ER ligands that have tissue-selective mixed agonist/antagonist activity, also suppressed EAE.…”
Section: Discussionsupporting
confidence: 76%
“…(E2) on EAE induction in ER-mutant mice clearly showed that this protective effect of E2 was mediated through ERa but not ERb [6][7][8]. Altogether, these studies support a protective role of estrogens on EAE that could explain the protective effect of pregnancy on MS [9].…”
supporting
confidence: 63%
“…Both ER␣ and ER␤ are expressed in lymphoid organs. Although there are some reports of differential ER␣ and ER␤ expression by immune cells, the relative roles of ER␣ and ER␤ in myeloid cell regulation remain poorly understood (12)(13)(14)(15)(16).…”
Section: Angerhans Cells (Lc)mentioning
confidence: 99%